Temperature dependence of the HartRAO pointing model - Copley, Charles Judd (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2008)
This thesis investigates control aspects of the Hartebeeshoek Radio Astronomy Observatory (HartRAO) antenna. The installation of a new 22 GHz receiver has required the pointing accuracy to be improved to less than 4 mdeg. The effect of thermal conditions on the the HartRAO antenna pointing offset is investigated using a variety of modelling techniques including simple geometric modelling, neural networks and Principal Component Analysis (PCA). Convincing results were obtained for the Declination pointing offset, where applying certain model predictions to observations resulted in an improvement in Declination pointing offset from 5.5 mdeg to 3.2 mdeg (â‰ˆ50%). The Right Ascension pointing model was considerably less convincing with an improvement of approximately from 5.5 mdeg to 4.5 mdeg (â‰ˆ20%) in the Right Ascension pointing offset. The Declination pointing offset can be modelled sufficiently well to reduce the pointing offset to less than 4 mdeg, however further investigation of the underlying causes is required for the Right Ascension pointing offset.
Keywords: Astronomical instruments; Observatories -- South Africa; Telescopes; Astronomical observatories; Astronomy -- Data processing; Antennas (Electronics)